The Effect of CSR Disclosure and Public Ownership on Financial Performance of Plantation Companies Listed on Indonesia Stock Exchange (2020-2023) - Intan Dewita Situmorang; Dimita H.P Purba; Rimky Mandala Putra Simanjuntak; Merry Anna Napitupulu (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
This research investigates how corporate social responsibility initiatives and public ownership structures influence financial outcomes among plantation firms listed on Indonesia's Stock Exchange during 2020-2023. The study examines the relationship between these two independent factors and company financial performance metrics as the dependent variable. From a total population of 36 plantation companies listed on the IDX, researchers employed purposive sampling techniques to identify 11 firms meeting specific inclusion criteria. The analytical approach utilized classical assumption testing methodology to evaluate the data.Findings reveal that while corporate social responsibility demonstrates a positive relationship with financial performance, this correlation lacks statistical significance. Conversely, public share ownership exhibits both a positive and statistically significant impact on financial outcomes.